The Impacts of Motocross Event on the Social, Economic, and Environmental Conditions of the Alue Kambuk Village, Nagan Raya Community - Masni, Melly; Marlinda; Futhira, Farah; Pratiwi, Syadillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
A district championship grasstrack and motocross event known as